Elevated exposures to persistent endocrine disrupting compounds impact the sperm methylome in regions associated with autism spectrum disorder - Maggio, Angela G.; Shu, Henry T.; Laufer, Benjamin I.; Bi, Chongfeng; Lai, Yinglei; LaSalle, Janine M.; Hu, Valerie W. (Frontiers in Genetics, 2022)
Environmental exposures to endocrine disrupting compounds (EDCs) such as the organo-chlorines have been linked with various diseases including neurodevelopmental disorders. Autism spectrum disorder (ASD) is a highly complex neurodevelopmental disorder that is considered strongly genetic in origin due to its high heritability. However, the rapidly rising prevalence of ASD suggests that environmental factors may also influence risk for ASD. In the present study, whole genome bisulfite sequencing was used to identify genome-wide differentially methylated regions (DMRs) in a total of 52 sperm samples from a cohort of men from the Faroe Islands (Denmark) who were equally divided into high and low expo-sure groups based on their serum levels of the long-lived organochlorine 1,1-dichloro-2,2-bis(p-chlorophenyl)ethylene (DDE), a primary breakdown product of the now banned insecticide dichlorodiphenyltrichloroethane (DDT). Aside from being consid-ered a genetic isolate, inhabitants of the Faroe Islands have a native diet that potentially ex-poses them to a wide range of seafood neurotoxicants in the form of persistent organic pol-lutants (POPs). Gene ontology, functional, and pathway analyses of the DMR-associated genes showed significant enrichment for genes involved in neurological functions and neu-rodevelopmental processes frequently impacted by ASD. Notably, these genes also signifi-cantly overlap with autism risk genes as well as those previously identified in sperm from fathers of children with ASD in comparison to that of fathers of neurotypical children. These results collectively suggest a possible environmental mechanism for introducing ASD-associated epigenetic changes into the sperm methylome which may have the potential for transgenerational inheritance.